Aktivitas Gel Ekstrak Daun Mengkudu (Morinda citrifolia) Terhadap Pertumbuhan Bakteri Penyebab Jerawat Staphylococcus epidermidis - Claudya Claudya; Rena Meutia; Yolanda Eliza Putri Lubis (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Noni (Morinda citrifolia L.) is a plant that contains several chemistry compounds including flavanoids, saponins, tannin, Polyphenols and terpenoids as an antibacterial. The purpose of this study was to determine the ethanolic extract of noni (Morinda citrifolia L.) can be formulated into antibacterial gel preparations and inhibit the growth of Staphylococcus epidermidis bacteria and to determine the concentration of ethanolic extract of noni (Morinda citrifolia L.) can inhibit growth of Staphylococcus epidermidis bacteria. This research was conducted experimentally with evaluation of gel preparations and testing of antibacterial activity against concentration of 10 mg/ml, 15 mg/ml, 20 mg/ml, 25 mg/ml, 30 mg/ml, positive control, and negative control. The research results on the evaluation gel preparation with concentration of 10 mg/ml, 15 mg/ml, 20 mg/ml, 25 mg/ml, 30 mg/ml meet the gel preparation requirements as well as antibacterial acitivity tests, namely Staphylococcus epidermidis with a concentration of 10 mg/ml inhibiton zone 8 mm (weak), 15 mg/ml inhibiton zone 10,9 mm (medium), 20 mg/ml inhibition zone 16,75 (strong), 25 mg/ml inhibiton zone 12,1 mm (medium), and 30 mg/ ml inhibition zone 13,4 mm (medium). Conclusion : it was concluded that for a concentration of 20mg/ml with the highest diameter of the inhibition zone against Staphylococcus epidermidis bacteria